Implementing Weekly Performance Stage (WPS) to Improve Speaking Skill and Creativity - Gusti Wildayani (Nusantara Science and Technology Proceedings, 2024)
Lack of speaking skill as one of the important language skills certainly influences communication competence and indirectly impacts the goal of preparing human resources for the 21st century who is capable in six competences such as characters, critical thinking, creativity, collaboration, communication, and citizenship. Researcher believes that Weekly Performance Stage (WPS) was one of the alternative methods of teaching which enables to support and motivates students to improve their speaking skills and creativity. Therefore, the research was to study how Weekly Performance Stage (WPS) was implemented to improve speaking skill and creativity. This idea raised from the principle of Differentiated Learning in Kurikulum Merdeka and Project Based Learning. The research has been done as the Classroom Action Research consisted of 6 meetings in the IX A Grade SMPN 1 Martapura. Along the study, the researcher had collected data by performing observation, performance assessment, and written form. The research findings were 80% students indicated in the very good and good categories of ability in speaking while 100% students had achieved more than minimum mastery score (?75) for understanding the lesson and creativity. Therefore, WPS is highly recommended for any teachers for improving students’ speaking skill and creativity. The researcher intentionally expects this research will raise other creative ideas and inspires other English teachers for facilitating students by meaningful and enjoyable learning.